RIFM fragrance ingredient safety assessment, Fenchyl alcohol, CAS registry number 1632-73-1. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Abstract: The use of this material under current use conditions is supported by the existing information. This material was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, as well as, environmental safety. Repeated dose toxicity was determined to have the most conservative systemic exposure derived NO[A]EL of 15 mg/kg/day. A gavage 13-week subchronic toxicity study conducted in rats on a suitable read across analog resulted in a MOE of 10, 714 while assuming 100% absorption from skin contact and inhalation. A MOE of >100 is deemed acceptable. Highlights: Fenchyl acohol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to have the most conservative NO[A]EL. An acceptable MOE was obtained.